POTENSI BUAH NANGKA (Artocarpus heterophyllus L) SEBAGAI ANTIDIABETES IN VITRO - Khairina, Khairina; Suhartono, Eko; Biworo, Agung (Berkala Kedokteran, 2015)
Artocarpus species have been used by traditional medicine of Indonesian. It can be useful as anti-bacterial, anti-diabetic, anti-inflammatory, antioxidant and anti-helmintics. The present study was aimed to test the inhibitory glycated hemoglobin potency of aqueous extract of Jackfuit. This study is a quasi experimental research with non randomized method post test-only group design, which using a model reaction of two groups : extract jackfruit as the test group and glikazid as the control group, with each concentration of 10%, 20%, 30%. Potential inhibitor of glycated hemoglobin jackfruit as determining the amount of IC50. From this research got IC50 of jackfruit extracts is 56,43% (r=0,999) whereas for glikazid of 17.268 (r = 0.989). The value of r indicates a positive relationship between the concentration and the inhibitor glycated hemoglobin potential. These results indicate that the extract of Jackfruit has potential as an inhibitor glycated hemoglobin. Keywords: glycated hemoglobin, jackfruit, Artocarpus heterophllus L, glikazid.